Reconfigurable Web-Interface Remote Lab for Instrumentation and Electronic Learning - Sierra-Fernandez, Jose María; Florencias-Oliveros, Olivia; Espinosa-Gavira, Manuel Jesús; Palomares-Salas, José Carlos; Agüera-Pérez, Agustín; González-de-la-Rosa, Juan José (International Journal of Online and Biomedical Engineering (iJOE), 2020)
Lab sessions in engineering education are designed to reinforce theoretical concepts. However, usually there are not enough time to reinforce all of them. Remote and virtual lab give students more time for reinforce those concepts. In particular, with remote labs, this can be done interacting with real lab equipment and specific configurations. This work proposes a flexible configuration for Remote Lab Sessions, based on some of 2019 most popular programming languages (Python and JavaScript). This configuration needed minimal network privileges, it is easily to scale and reconfigure. Its structure is based on a unique Reception-Server (which hosts User database, and Time Shift Manager, it is accessible from The Internet, and connect Users with Instruments-Servers) and some Instrument-Servers (which manage hardware connection and host experiences). Users always connect to Reception-Server, and book a shift for an experience. During the time range associate to that shift, User is internally forwarded to Instrument-Server associated with selected experience, so User is still connected to Reception-Serer. In this way, Reception-Server acts as a firewall, protecting Instrument-Servers, which never are open to The Internet. A triple evaluation system is implemented, User session logging and auto-evaluation (objectives accomplished) a knowledge test and an interaction survey. An experience is implemented, controlling a DC source using Standard Commands for Programmable Instruments.